IMPLEMENTASI MODEL PEMBELAJARAN KONSTRUKTIVISME DALAM MENINGKATKAN HASIL BELAJAR SISWA DALAM PENDIDIKAN AGAMA ISLAM PADA KOMPETENSI DASAR BERIMAN KEPADA QADA DAN QADAR BERBUAH KETENANGAN HATI - Annilta Manzilah 'Adlimah (POTENSIA: Jurnal Kependidikan Islam, 2019)
The main problem in this study is the low learning outcomes of students of class XI F in teh second semester of SMP N 1 Limpung Batang in academic year 2018/2019 on Islamic Education subjects. One factor that causes low student ability is the teaching method that has been used so far tends to make students passive and teacher-centered. To improve student learning outcomes, the researchers applied the constructivism approach in teaching PAI in class XI F of SMP N 1 Limpung, Batang in the theme of “Beriman Kepada Qada dan Qadar Berbuah Ketenangan Hati.” Which became the focus of research for students of class XI F, amounting to 33 students. Research location at Limpung 1 Junior High School in Batang Regency. This research is a classroom action research, carried out in 2 cycles, each cycle consisting of 4 stages: planning, action, observation, and reflection. From the results of Cycle 1 actions, the classical learning completeness was 70% with an average score of 72.78. Cycle 2 results obtained 97% classical learning completeness with an average value of 84.88. Thus it can be concluded that the implementation of constructivism learning models can improve the learning outcomes of class XI F students of SMP N 1 Limpung Batang Regency.